The use of the Bayes factor for statistical inference (Letter to the Editor) - Ramos-Vera, C. A.; Oluwaseun Ogundokun, R. (Journal of Human Sport & Exercise, 2021)
The use of the Bayes factor is essential for statistical inference in frequent estimation tests (for example, correlation analysis, statistical test of comparison of student t means, among others). Therefore, the practice of replicable findings that generate more credible conclusive evidence in sports science research using Bayesian inference as recommended by Ly, Raj, Etz, Gronau & Wagenmakers, 2018; Marsman & Wagenmakers, 2017.